PENGARUH LEVERAGE, SIZE, GROWTH DAN MODAL KERJA TERHADAP PROFITABILITAS - Lestari, Anis Puji; Hermanto, Suwardi Bambang (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
The purpose of this research is to test the influence of leverage, size, growth, and work capital to the profitability on the go public companies which are listed in Indonesia Stock Exchange in 2010-2013 periods in the group of consumer goods industry. The sample collection has been done by using purposive sampling method to the 38 consumer goods industry companies and 26 companies with 104 financial statements which meet the sample criteria have been obtained to be analyzed. The analysis technique has been done by using Multiple Regression Analysis and the independent variables i.e.: Leverage (LEV), Size (SIZ), Growth (GRO), Work Capital (MKE) and the dependent variable i.e.: Profitability (PRO). The result of the research shows that size (SIZ) and growth (GRO) variable has positive and significant influence to the profitability (PRO) whereas leverage (LEV) variable has negative and significant influence to the profitability (PRO). Meanwhile work capital (MKE) variable has negative and not significant influence to the profitability (PRO). The result of multiple regression tests has obtained R2 by 0.519 or 51.9%, meanwhile the remaining 48.1% is influenced by other variables.Keywords: Profitability, Leverage, Size, Growth, Work Capital.